Aktivitas Invitro Senyawa Antimikroba Streptococcus lactis (INVITRO ACTIVITY ANTIMICROBIAL SUBSTANCE PRODUCED BY STREPTOCOCCUS LACTIS) - I Nyoman Suarsana; Maria Bintang; Iwan Harjono Utama; Ni Gusti Agung Ayu Suartini (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2001)
Aktivitas Invitro Senyawa Antimikroba Streptococcus lactis (INVITRO ACTIVITY ANTIMICROBIAL SUBSTANCE PRODUCED BY STREPTOCOCCUS LACTIS)